PENGARUH KUALITAS PRODUK, WORD OF MOUTH, DAN PRESEPSI HARGA DAN TERHADAP PEMBELIAN PRODUK SKINCARE DI KOTA BATURAJA - Rini Purnama; Fifian Permata Sari; Munajat , Munajat (Media Bina Ilmiah, 2025)
This study aims to analyze the influence of product quality, word of mouth, and price perception on purchasing decisions for MS Glow skincare products in Baturaja City. This study uses a quantitative method with data collection techniques through questionnaires distributed to consumers of MS Glow Baturaja Branch. Data analysis was carried out using multiple linear regression with partial tests (t-test) and simultaneous tests (F-test). The results showed that product quality variables did not have a significant effect on purchasing decisions. Meanwhile, word of mouth had a positive and significant effect on purchasing decisions and price perception variables had a positive and insignificant effect on purchasing decisions. These findings indicate that consumers in Baturaja City are more influenced by recommendations and information from others in making purchasing decisions than price or product quality factors. Therefore, MS Glow is advised to strengthen its word of mouth strategy through customer reviews, user communities, and collaboration with local influencers. In addition, companies need to communicate product value more effectively to improve price and quality perceptions.